Towards Tailings Recycled Production Technologies - Palominos-Villavicencio, F (Institute of Electrical and Electronics Engineers Inc., 2021)
This paper studies the potentialities of tailings recycling. A bibliographic review identifies the advantages and disadvantages of the business worldwide, the minerals that are extracted from the deposits, the technologies that are produced with the tailings and the markets in which they are commercialized. A case study is presented in which the amount of minerals in a sample is analyzed, as well as the projects that have been developed for recycling and transformation into technological products. Finally, possible scenarios are analyzed and conclusions are drawn on more efficient sustainability opportunities that reduce environmental risks. © 2021 IEEE.